A Linguistic Analysis of Posuban as a Material Culture: The Case of Amamoma, Apewosika and Kwaprow (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of the study was to find out the interpretations of colours and symbols on the Posuban as well as interpretations of the inscriptions on Posuban as an object of material culture and identity. The study employed a qualitative research design. Observation and interview were the instruments used to collect data for the study. From the linguistic perspective of colours, drawings/images and inscriptions it was revealed that, Posuban tells a lot about Fante peoples’ history, beliefs, values and their character which remain otherwise inaccessible except through impersonal records. It was also revealed that Posuban is emblematic, iconic and indexical. It is therefore recommended that, more studies should be done on Posuban. This is because, today, Posuban are merely considered as shrines but there are a lot of scholarly information that could be obtained from this Posuban for studies in so many disciplines